PENGELOLAAN SAMPAH MEDIS DI RSUD Dr.H. SLAMET MARTODIRDJO PAMEKASAN TAHUN 2012 - Rahmi Megarina Istighfarin; M Muchson; Darjati . (Poltekkes Kemenkes Surabaya, 2013)
Dr.H.Slamet Martodirjo hospital in Pamekasan is classified as a Type B Non-educational hospital. Problemsdiscovered at the hospital involve infrastructural items such as special trolley bins, delayed supply of fuel formedical waste incinerators, long distance to be covered from wards to the incinerator, accumulating medicalwastes in wards, temporary holding sites for wastes not available, lack of awareness among workers inhandling medical and non-medical wastes, medical waste management personnel seldom wear personalprotective devices. This hospital needs to address these problems in order for it to become better and moreadvanced hospital.This is a descriptive study, primary data were obtained through observation and interviews, while secondarydata were retrieved from records kept by the hospital.Based on the findings, the average amount of medical waste generated by this hospital every day was 34.5Kg. At the waste generation stage all aspects seemed to meet the requirements since there is a sufficientcapacity to accommodate the wastes, the same applies to the garbage collection phase since wastes areseparated between medical and non-medical wastes. In performing their garbage collection tasks, workersseldom wear their personal protective devices and such practice could put themselves in dangerous situation.Support to medical waste management is quite adequate, this includes aspects of organizing, financing,workforce, equipment / supplies, record keeping and evaluation.The study concluded that management of medical waste at the Dr.l-l.Slamet Martodirjo hospital have met thedesignated requirements. The study recommended that medical waste workers wear their personal protectivedevices, provided with proper tools and infrastructures especially proper trolleys for transporting wastes.Keywords: medical waste